SOCIAL NETWORKS AND EDUCATION: THE INCREASE IN STUDENT LEARNING EFFICIENCY AND THE SEARCH FOR MEANS OF CONTROL - Golubeva, Tatyana; Kokhanovskaya, Indira; Golovneva, Elena; Fatykhova, Alevtina; Terekhova, Natalya (Revista Inclusiones, 2020)
The total informatization of a society leads to the wide popularization of social networks. A growing number of people in the world can use social networks with any device, which simplifies and improves the process of online communication. Social networks provide an opportunity for free, cheap, simple, and direct contact with the student audience. They help enter discussions, explore new topics, acquire and maintain new knowledge and skills, assess one’s work and the work of one’s colleagues, and think critically. The article considers the features of social networks and analyzes their capabilities (main advantages) in student education. The analysis of possibilities and readiness of university professors and students to involve social networks in the educational process is carried out. A SWOTanalysis of the involvement of social networks in the educational process is given. The benefits and limitations of IT in the educational process for different categories of users are considered. Tools and examples of using social networks are presented. The article also considers the ways of organizing control and analysis of student progress using social services and networks.